(untitled) (Tanzania Medical Journal, 2024)
Introduction The quality of pharmaceutical care is affected by the nature of the drug dispensing system in a facility. This study evaluated the effectiveness and operational labor costs between traditional drug dispensing systems (TDDS) and Unit Dose Drug Dispensing Systems (UDDS) at a tertiary hospital in Tanzania. Methods A comparative mixed-method cross-sectional study was conducted at Muhimbili National Hospital involving patients and healthcare professionals (HCPs). Data for medication errors, missed doses, dispensing times, and operational labor costs were collected in standardized collection forms. Qualitative data was collected through in-depth interviews. Thematic analysis was used for qualitative data, while descriptive statistics were used for quantitative data. Comparisons were done by using a t-test, X2 test, and Odds Ratio (OR), a p-value <0.05 was considered for statistical significance. Results The study enrolled 243 patients, finding that patients using TDDS were 16.6 times more likely to miss a dose. Labour costs were statistically significantly higher in UDDS than in TDDS (p=0.003). Also, UDDS had a higher number of patients with medication errors (54.7%) compared to TDDS (45.3%). The average dispensing time was longer (96 minutes) in UDDS compared to 72 minutes in TDDS. HCPs perceived UDDS as a more effective dispensing system than TDDS through improving inter-professional relationships and drug availability to patients. Conclusion The unit-dose dispensing system effectively reduces missed doses and enhances drug availability to patients and inter-professional relationships but incurs higher labor costs than the traditional dose dispensing system. Its use in other healthcare settings is recommended after operational cost improvement.